Dynamics Control of the Complex Systems via Nondifferentiability - Carmen Nejneru; Anca Nicuţă; Boris Constantin; Liliana Rozemarie Manea; Mirela Teodorescu; Maricel Agop (Journal of Applied Mathematics)
A new topic in the analyses of complex systems dynamics, considering that the movements of complex system entities take place on continuum but nondifferentiable curves, is proposed. In this way, some properties of complex systems (barotropic-type behaviour, self-similarity behaviour, chaoticity through turbulence and stochasticization, etc.) are controlled through nondifferentiability of motion curves. These behaviours can simulate the standard properties of the complex systems (emergence, self-organization, adaptability, etc.).